2016
DOI: 10.1021/acsnano.6b05577
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Properties of a Two-Dimensional Silica Kagome Lattice

Abstract: Kagome lattices are structures possessing fascinating magnetic and vibrational properties, but in spite of a large body of theoretical work, experimental realizations and investigations of their dynamics are scarce. Using a combination of Raman spectroscopy and density functional theory calculations, we study the vibrational properties of two-dimensional silica (2D-SiO2), which has a kagome lattice structure. We identify the signatures of crystalline and amorphous 2D-SiO2 structures in Raman spectra and show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
3
21
1
Order By: Relevance
“…Mode A g (7) corresponds to the well-known torsional mode observed in 2D kagome lattices [55][56][57]. As depicted in Fig.…”
Section: B Vibrational Propertiesmentioning
confidence: 82%
“…Mode A g (7) corresponds to the well-known torsional mode observed in 2D kagome lattices [55][56][57]. As depicted in Fig.…”
Section: B Vibrational Propertiesmentioning
confidence: 82%
“…In addition, we distort the crystal structures by creating a rotated Kagome lattice similar to ref. 56 , and structural relaxation at different electric fields always removes the rotation distortion. Experimentally it has been found that both monolayer silicate and bilayer silica can be grown on various substrates with biaxial strains varying from −5.6 to 5.7% 44,48,52,53,64,65 .…”
Section: Resultsmentioning
confidence: 97%
“…The experimental realisation of monolayer Kagome silicates can be dated back to the 1990s 43 , but more recently various synthesis strategies have been developed to obtain 2D Kagome silicate or silica on multiple substrates [44][45][46][47][48] . These developments enable researchers to study the structural [49][50][51][52][53][54][55] , vibrational [56][57][58] , electronic [59][60][61] , mechanical 62,63 , and chemical properties 64 of this material family and to explore the various physical phenomena associated with 2D Kagome lattices.…”
Section: Resultsmentioning
confidence: 99%
“…We provide evidence of such an exotic 2D Si allotrope through scanning tunneling microscopy (STM) observations, high-resolution core-level (CL) and angle-resolved photoelectron spectroscopy (ARPES) measurements, along with Density Functional Theory calculations.The two-dimensional Kagome lattice, which consists in corner-sharing rigid triangles, possesses fascinating magnetic properties and an exotic correlated electronic structure, possibly hosting Dirac electronic states [1,2], that could lead to a topological insulator [3]. On-surface Kagome lattices are often engineered in 2D metal-organic systems [ 4]; they might be tailored also using a molecular pattern [5]. Rare examples concern experimentally realized inorganic networks [6].…”
mentioning
confidence: 99%